2020
DOI: 10.1002/jat.4048
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of potential early key events and mode of action for 1,2‐dichloroethane‐induced mammary tumors in female rats

Abstract: 1,2‐dichloroethane (DCE or EDC) is a chlorinated hydrocarbon used as a chemical intermediate, including in the synthesis of polyvinyl chloride. Although DCE has induced tumors in both rats and mice, the overall weight‐of‐evidence suggests a lack of in vivo mutagenicity. The present study was conducted to explore a potential mode of action further for tumor formation in rat mammary tissue. Fischer 344 rats were exposed to target concentrations of 0 or 200 ppm of DCE vapors (6 hours/day, 7 days/week) for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Regarding carcinogenic mechanisms, a 28-day inhalation study in rats following 1,2-dichloroethane exposure (LeBaron et al, 2021) reported negative results in the comet assay and DNA adduct tests in mammary glands and liver, and no genotoxic effects or specific DNA adducts associated with carcinogenesis in the mammary tissue were detected. However, the compound was positive for DNA binding ability in vitro (Cheever et al, 1990;Reitz, 1980Reitz, , 1982 and in vivo studies (Banerjee, 1988;Arfellini et al, 1984;Baertsch et al, 1991).…”
Section: Toxicological Mechanismsmentioning
confidence: 99%
“…Regarding carcinogenic mechanisms, a 28-day inhalation study in rats following 1,2-dichloroethane exposure (LeBaron et al, 2021) reported negative results in the comet assay and DNA adduct tests in mammary glands and liver, and no genotoxic effects or specific DNA adducts associated with carcinogenesis in the mammary tissue were detected. However, the compound was positive for DNA binding ability in vitro (Cheever et al, 1990;Reitz, 1980Reitz, , 1982 and in vivo studies (Banerjee, 1988;Arfellini et al, 1984;Baertsch et al, 1991).…”
Section: Toxicological Mechanismsmentioning
confidence: 99%
“…Thus, the production of one ton of vinyl chloride is accompanied by the appearance of nearly 50 kg of organochlorine wastes, represented by a complex mixture of chlorinated derivatives of ethane and ethylene. All these substances are xenobiotics, i.e., they are foreign to the body or to an ecological system and therefore exert highly toxic effects on living forms, including humans [3][4][5].…”
Section: Introductionmentioning
confidence: 99%